The change and influence mechanism of the mechanical properties of tricalcium silicate hardening at high temperature. (15th November 2021) - Wei, Tingcong; Cheng, Xiaowei; Gu, Tao; Huang, Sheng; Zhang, Chunmei; Zhuang, Jia; Zheng, Youzhi
Highlights: The microhardness of hardened C3 S decreased as curing temperature increased. As curing temperature increased, high calcium-silicon ratio phases increased. 200 °C was an abrupt retrogression point of mechanical properties. Sudden increase in hillebrandite content was a key factor for abrupt retrogression. Abstract: Tricalcium silicate (C3 S) accounts for 48–65% of the quality of oil-well cement. The properties of oil-well cement are closely related to the hydration characteristics of C3 S. To further understand the reason for the mechanical property decline of oil-well cement at high temperature, starting from C3 S, this research analyses the hydration of C3 S at different temperatures (150 to 230 °C). The evolution of C3 S hydration products was characterized by X-ray diffraction, thermogravimetric analysis and scanning electron microscopy. The results prove that, with increasing of temperature, the content of portlandite decreases. The content of acicular hillebrandite first increased and then decreased, and reached a maximum of 49% at 200 °C. Fibrous jaffeite and granular reinhardbraunsite were produced together, and the content increased synchronously. Vickers hardness tests show that the microhardness of hydrated C3 S decreased continuously as the curing temperature increased. Specifically, at 200 °C, the microhardness was reduced by 53%, which is an abrupt retrogression point of mechanical properties. The mechanical properties decreased because, for hillebrandite, jaffeite and reinhardbraunsite tend to form high-permeability and low-strength structures. At 200 °C, the abrupt increase in hillebrandite content and the formation of new phases were key factors leading to the abrupt change in mechanical properties.